The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 19th Symposium on Interactive 3D Graphics and Games 2015
DOI: 10.1145/2699276.2699287
|View full text |Cite
|
Sign up to set email alerts
|

Position-based fluid control

Abstract: Figure 1: An animated dancer made of fluid using our position-based fluid control method. AbstractWe present a novel fluid control method that is capable of driving particle-based fluid simulation to match a rapidly changing target while keeping natural fluid-like motion. To achieve the desired behavior, we first generate control particles by sampling the target shape and then apply a non-linear constraint to each control particle, with its neighboring fluid particles keeping a constant fluid density within it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…For more complex turbulent flows, a spatial‐temporal varying synthesis approach was proposed to obtain fine‐scale fluid details . Recently, it was shown that position‐based fluid control can be achieved in real time . However, in contrast to the target shape control, the involvement of fluid motion during the design process could be more difficult.…”
Section: Related Workmentioning
confidence: 99%
“…For more complex turbulent flows, a spatial‐temporal varying synthesis approach was proposed to obtain fine‐scale fluid details . Recently, it was shown that position‐based fluid control can be achieved in real time . However, in contrast to the target shape control, the involvement of fluid motion during the design process could be more difficult.…”
Section: Related Workmentioning
confidence: 99%
“…However, the grid‐based fluid control based is relatively computational complex, which is restricted from fixed simulation domain. There are also some control methods on particle‐based fluid such as in other works . Thürey et al used the control force for coarse control, that is, the control force attracts the SPH particles to control the fluid to fill the control target or to flow along the specified path.…”
Section: Related Workmentioning
confidence: 99%
“…Comparison of the control results for a fast‐moving fluid ball among different methods: (a) without spring force, (b) with spring force from the work of Zhang et al, and (c) with our method. (a) Many SPH particles fly out of the ball shape when the control particles of ball move in the pool.…”
Section: Our Algorithmmentioning
confidence: 99%
“…Fluid particles can match the special target shape by the effect of control force. In this paper, the control force includes coarse control force, spring constraint force, and velocity constraint force . The coarse control force is used to attract fluid particles to match the target shape.…”
Section: Algorithmmentioning
confidence: 99%
“…In this paper, the control force includes coarse control force, 2 spring constraint force, 23 and velocity constraint force. 2,23 The coarse control force is used to attract fluid particles to match the target shape. The spring constraint force takes effect only when the fluid particle is far from its corresponding control particle to avoid introducing artificial viscosity.…”
Section: Detail Preserving Via Control Force Transfer 331 Control Fmentioning
confidence: 99%